Contentious Politics in Afghanistan and the U.S. Efforts for Peace (2008-2018) - Rana Eijaz Ahmad (Journal of Political Studies, 2018)
Afghanistan has been a battlefield for big powers for last four decades. In 1979, Russia invaded in Afghanistan and the U.S. fought a proxy war in the region with the help of Pakistan. Russian withdrawal of forces from Afghanistan under Geneva accord in 1988 caused disintegration of the former Soviet Union in 1991. The Taliban government emerged in Afghanistan in 1994 and a regime of contentious politics started in Afghanistan. It allegedly caused terrorism at local as well as international level. The U.S. alienated itself from the region after the Soviet withdrawal from Afghanistan. In September 2001, Osama Bin Laden purportedly attacked the U.S. security hub Pentagon and economic hub World Trade Centre. America retaliated with cruise missile and invaded in Afghanistan in 2001. After the U.S. claim for killing Osama in May 2011 in Abbotabad, Pakistan, decided to withdraw its forces from Afghanistan in 2014. The U.S. wishes to sustain peace in the region after its withdrawal. It intends to ensure all the conflicting parties that they should come on table for a peaceful bargaining. The U.S. is rehabilitating Afghanistan with her allies. Afghanistan was destructed during the war on terror. This paper is based on the theory of contentious politics introduced by three American sociologists, Sidney Tarrow, Charles Tilly, and Doug McAdam. The tipping point theory is also used in the backdrop of 9/11 incident. It is explained with primary as well as secondary sources.